(3QSGdI aj eYfi GdLhgQ GdaQO hGdgjhdi hGdLSes - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg ,hHYO CjgG GdCHf GdcQje , CYRc Gddg HYR GdWGYI hEJHGY GdOjf GdeSJbje , aEfc SCdJfi Yf eYfi GdLhgQ hGdgjhdi hGdLSe , hPcQJ Cf Pdc bO ghd efc s
(3BNQgG (B:s
(3hJCed ajgG hJMbjb aEfgG JfaYc ai ehGVY GdYdhe GdJYbdjI hGdfbdjI hcJH ebjOkG dcdGe SGOGJg eY JUQa ajg djQLY Edi Pdc YfO GdMGLI Edjg NOjege eMeO GdSYjO Hf eMi GdOjf GdMSfi HChGFd ThGd YGe (B1276 (3ef GdgLQI GdfHhjI Ydi UGMHgG CaVd (B( (3GdSdGe (B) (3HGdUdGIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs